Chemoresistive materials for electronic nose: Progress, perspectives, and challenges. Issue 3 (15th August 2019) - Park, Seo Yun; Kim, Yeonhoo; Kim, Taehoon; Eom, Tae Hoon; Kim, Soo Young; Jang, Ho Won
Abstract: An electronic nose (e‐nose) is a device that can detect and recognize odors and flavors using a sensor array. It has received considerable interest in the past decade because it is required in several areas such as health care, environmental monitoring, industrial applications, automobile, food storage, and military. However, there are still obstacles in developing a portable e‐nose that can be used for a wide variety of applications. For practical applications of an e‐nose, it is necessary to collect a massive amount of data from various sensing materials that can transduce interactions with molecules reliably and analyze them via pattern recognition. In addition, the possibility of miniaturizing the e‐nose and operating it with low power consumption should be considered. Moreover, it should work efficiently over a long period of time. To satisfy these requirements, several different chemoresistive material platforms including metal oxides, organics such as polymers and carbon‐based materials, and two‐dimensional materials were investigated as sensor elements for an e‐nose. As an individual material has limited selectivity, there is a continuing effort to improve the selectivity and gas sensing properties through surface decoration and compositional and structural variations. To produce a reliable e‐nose, which can be used for practical applications, researches in various fields have to be harmonized. This paper reviews the progress of research on e‐noses based on a chemoresistive gas sensor array and discusses the inherent challenges and potential solutions. Abstract : Oxides, metals, polymers, and 2D materials have emerged as promising materials for the electronic nose. Recent significant developments of the electronic nose are reviewed with a focus on the sensing materials, characteristics, and applications. The future challenges and prospects in developing a semiconductor gas sensor array based electronic nose are discussed.